2017
DOI: 10.1016/j.jadohealth.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

History of Overweight/Obesity as Predictor of Care Received at 1-year Follow-Up in Adolescents With Anorexia Nervosa or Atypical Anorexia Nervosa

Abstract: Our findings suggest that, despite greater degree of weight loss and no difference in duration of illness, participants with a history of overweight/obesity are less likely to receive inpatient medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 21 publications
1
47
1
1
Order By: Relevance
“…In adolescents and young adults with restrictive eating disorders, the prevalence of a history of overweight or obesity ranges from 19.3% to 36.7%. [3][4][5] These numbers mirror the national prevalence of overweight or obesity, suggesting that patients with higher weight status are as likely to experience disordered eating as their normal-weight peers. 4 Indeed, overweight adolescents report greater concern about their weight and more body dissatisfaction than their normal-weight peers.…”
Section: ■ Common and Underrecognizedmentioning
confidence: 94%
See 4 more Smart Citations
“…In adolescents and young adults with restrictive eating disorders, the prevalence of a history of overweight or obesity ranges from 19.3% to 36.7%. [3][4][5] These numbers mirror the national prevalence of overweight or obesity, suggesting that patients with higher weight status are as likely to experience disordered eating as their normal-weight peers. 4 Indeed, overweight adolescents report greater concern about their weight and more body dissatisfaction than their normal-weight peers.…”
Section: ■ Common and Underrecognizedmentioning
confidence: 94%
“…2 Although one study reported that a higher percentage of men with eating disorders had a history of premorbid overweight than women, another found no difference by sex. 3,4 Traditionally, restrictive eating disorders were characterized by low weight or failure to grow appropriately within expected growth curves, maladaptive weight loss strategies, and fear of weight gain. However, these criteria were modifi ed in the fi fth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), demonstrating the evolving clinical understanding of restrictive eating disorders.…”
Section: ■ Common and Underrecognizedmentioning
confidence: 99%
See 3 more Smart Citations